(untitled) (Innovative professional education, 2025)
The article analyzes the main advantages of automated testing, such as objectivity, accuracy, time and resource savings, and the possibility of quick feedback. Particular attention is paid to adaptive testing, which allows individualizing the learning process and increasing students’ motivation. The challenges associated with the implementation of automated testing are highlighted. Attention is drawn to the importance of using e-learning resources and automated testing to improve the quality of the educational process in vocational education institutions.